Work Stress and its influence on the work - Atalaya P., María (2001)
The article analyzes the various theoretical approaches to stress at work, describing how the episode of stress develops. Generating sources of occupational stress and its effects on health and performance of workers is. also; it is about the sensitivity of some jobs to stress. posed various strategies to address the problem, the first exclusive which are complementary. The conclusion emphasizes the effectiveness of a solution that integrates both the organization and the workforce, as principal actors.